Central exit examinations increase performance ...: But take the fun out of mathematics - Hendrik Jürges; Kerstin Schneider (University of Wuppertal, Schumpeter School of Business and Economics, 2008)
In response to PISA, all German federal states but one have adopted central exit examinations (CEEs) at the end of all secondary school tracks. Theoretically, the advantages of CEEs are fairly undisputed. CEEs make teaching and learning output observable and comparable across schools, and provide incentives for teachers and students to increase their effort. In line with earlier research, we confirm that CEEs have a positive causal effect on student performance. We also investigate what actually drives this effect. We find that the teachers' main reaction to CEEs is to increase the amount of homework, and to check and discuss homework more often. Students report increased learning pressure, which has sizeable negative effects on student attitudes towards learning. Students who take central exit exams in mathematics like mathematics less, think it is less easy and they are more likely to find it boring.
urn:nbn:de:hbz:468-20080459
Keywords: I28; H42; D02; 330; High-stakes testing; student achievement; teacher quality; Schüler; Bildungsniveau; Absolventen; Mathematik; Zentralisierung; Deutschland